2014
DOI: 10.1080/19443994.2013.812522
|View full text |Cite
|
Sign up to set email alerts
|

Removal of trichloroethylene (TCE) from groundwater by GAC and ZVI

Abstract: A B S T R A C TDynamic and static test methods were used to investigate the removal efficiency of trichloroethylene (TCE) from ground water by different media of zero-valent iron (ZVI), two kinds of granular activated carbon (GAC), and a mixture of ZVI and GAC. The test results showed that ZVI, GAC, and the mixture of ZVI and GAC could effectively remove TCE. Under static conditions, the TCE removal rate by ZVI was 68.32%, the TCE removal rate by coconut shell GAC was 55.2%, and the TCE removal rate by ZVI + G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Commonly used material was cheap iron, iron could effective adsorb and decrease a variety of heavy metals and organic matters. The use of Fe(0)-PRBs for treating polluted groundwater was close to two decades;however, more researches were still required to provide sufficient information of reactive mechanisms about combined pollution of heavy metals and organic matter and predict long-term performance of PRBs [8][9][10]. The purpose of this paper is to evaluate the efficiency of iron pillar towards Cr(Ⅵ) and TCE removal, evaluate the sorts of elements on the iron surface through Scanning Electron Microscopy (SEM) and Energy-Dispersive Spectrometry (EDS).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used material was cheap iron, iron could effective adsorb and decrease a variety of heavy metals and organic matters. The use of Fe(0)-PRBs for treating polluted groundwater was close to two decades;however, more researches were still required to provide sufficient information of reactive mechanisms about combined pollution of heavy metals and organic matter and predict long-term performance of PRBs [8][9][10]. The purpose of this paper is to evaluate the efficiency of iron pillar towards Cr(Ⅵ) and TCE removal, evaluate the sorts of elements on the iron surface through Scanning Electron Microscopy (SEM) and Energy-Dispersive Spectrometry (EDS).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in drinking water treatment processes, few studies have been reported on the enhanced-ZVI process, such as the removal of trichloroethylene [23] and arsenic contamination [24], but only our previous study reported upon about how this enhanced process impacted NOM removal during drinking water production from surface waters [25].…”
Section: Introductionmentioning
confidence: 99%
“…The industrial solvent trichloroethylene (TCE) is among the most widespread chlorinated compounds found in groundwater contamination [1]. High levels of TCE is considered a likely human carcinogen [2] .…”
Section: Introductionmentioning
confidence: 99%